Alternative voices: a plurality approach for religious studies ; essays in honor of Ulrich Berner - Adogame, Afe; Echtler, Magnus; Freiberger, Oliver (Critical studies in religion, Religionswissenschaft, 2013)
"When scholarship presents the histories, belief systems, and ritual patterns of specific religious groups, it often privileges victorious and élite fractions of those communities to the detriment and neglect of alternative, dissonant, and resurgent voices. The contributions in this volume, which include case studies on various religions and academic contexts, illustrate the importance of listening to those alternative voices for the study of religion."--Back cover
Beitr. teilw. dt., teilw. engl
Keywords: Aufsatzsammlung; Festschrift; Religionswissenschaft; Religiöser Pluralismus